A Time-Sharing Program Library for Accounting Courses. - Lampe, James C. (The Accounting Review, 1971)
Abstract Many colleges and universities are purchasing small time-sharing systems, at relatively low cost. For example, IBM has introduced a new facility which permits up to 31 teletype connections and, when operated at minimum configuration, requires monthly operating costs of less than $8,000. Furthermore, business schools do not have their own computer, nor must they be connected with a large university which supports a computer. Commercial time-sharing is readily available from several sources, regardless of geographic location. Discounted rates are usually provided for educational use. Fixed costs are typically under $100 per month for the rental of teletype, including maintenance. Cost of operating terminals runs from about $8 to $13 per terminal hour of use, and are expected to be reduced with improvements in hardware and software. According to a survey reported in a recent issue of the journal Datamation, education is the fourth largest user of time-sharing. The increased availability of time-sharing systems and low entry cost have prompted many schools of business to obtain teletype terminals either by outright purchase or through rental contracts.